Learning Computing through Creating and Connecting. - Brennan, Karen (Computer (00189162), 2013)
Despite increased cultural awareness of computing, programming remains inaccessible to many young people. In response to this challenge, MIT Media Lab researchers are developing Scratch, which combines an authoring environment for interactive media projects with an online platform for sharing those projects. The first Web extra at http://youtu.be/2XiOK4OzAaE is a video overview of Scratch and ScratchEd, showing the authoring environment for interactive media projects as well as the sharing platform. The second Web extra at http://scratch.mit.edu/projects/editor/?tip_bar=getStarted helps visitors get started on their first Scratch activity where they can experience its authoring and sharing environments.